Sectoral and regional impacts of trade liberalization on the skilled-unskilled wage-gap in Pakistan - Jameel, Muhammad Awais; Hina, Hafsa; Ul-Haq, Jabbar (Edelweiss Applied Science and Technology, 2023)
This study explores the impacts of trade liberalization on the skilled-unskilled wage gap (henceforth SUSWG) by using the micro-level data of Pakistan. It is generally believed that when economies are liberalized, the SUSWG increases, especially in poor economies. Our study uses a two-step estimation methodology. We used two measures for SUSWG at sectoral and regional levels. We employed Oaxaca-Blinder decomposition for residual wage-gap, and log-wage-gap. For empirical (i.e., sectoral and regional) analysis, we employed Fixed effects (FE), Random effects (RE) and FE with Driscoll-Kraay Standard Errors (DKSEs), feasible generalized-least-squares (FGLS), and Panel-corrected Standard Errors (PCSE). We used sectoral panel data for sectoral analysis and provincial panel data for regional analysis, using the data from 1990 to 2005. Our study finds that protection rates and SUSWG are associated in Pakistan. Trade liberalization increases the SUSWG. The sectoral and regional analysis reveal similar findings on the impact of liberalization on SUSWG. Moreover, our results are robust and insensitive to various controls, measurement approaches (i.e., the log wage gap and the residual wage gap), and econometric techniques. We also find that lagged tariffs increase the SUSWG. Our findings will provide guidelines for policymakers to make future policies regarding trade liberalization and SUSWG in Pakistan.